An Unusual Presentation of Metastatic Squamous Cell Cervical Carcinoma Involving the Distal Ileum Mimicking Crohn's Disease. (1st October 1994) - Yoshida, Eric M; Chaun, Hugh; Swenerton, Kenneth D; Berean, Kenneth W; McGregor, Gregor I
Abstract : Both primary and secondary malignant diseases may present with a clinical, radiological and/or endoscopic picture resembling Crohn's disease. In this report, a 64-year-old woman previously treated surgically and with radiation for stage I B squamous cell carcinoma of the cervix presented with diarrhea and had endoscopic findings simulating Crohn's disease. Biopsies and subsequent laparotomy revealed that the lesions were metastatic cervical carcinoma involving the terminal ileum.